Effective treatment of levofloxacin wastewater by an electro-Fenton process with hydrothermal-activated graphite felt as cathode. (November 2020) - Liu, Jia-Ming; Ji, Zhi-Yong; Shi, Ya-Bin; Yuan, Peng; Guo, Xiao-Fu; Zhao, Li-Ming; Li, Shu-Ming; Li, Hong; Yuan, Jun-Sheng
Abstract: The performance of the cathode significantly affects the ability of the electro-Fenton (EF) process to degrade chemicals. In this study, a simple method to modify the graphite felt (GF) cathode was proposed, i.e. oxidizing GF by hydrothermal treatment in nitric acid. The surface physical and electrochemical properties of modified graphite felt were characterized by several techniques: scanning electron microscope (SEM), water contact angle, X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and linear scanning voltammetry (LSV). Compared with an unmodified GF (GF-0), the oxygen reduction reaction (ORR) activity of a modified GF was significantly improved due to the introduction of more oxygen-containing functional groups (OGs). Furthermore, the results showed that GF was optimally modified after 9 h (GF-9) of treatment. As an example, the H2 O2 generation by GF-9 was 2.26 times higher than that of GF-0. After optimizing the process parameters, which include the initial Fe 2+ concentration and current density, the apparent degradation rate constant of levofloxacin (LEV) could reach as high as 0.40 min −1 . Moreover, the total organic carbon (TOC) removal rate and mineralization current efficiency (MCE) of the modified cathode were much higher than that of the GF-0. Conclusively, GF-9 is a promising cathode for the future development in organic pollutant removal via EF. Graphical abstract: Effective treatment of levofloxacin wastewater by an electro-Fenton process with graphite felt modified by a simple and low-temperature hydrothermal-activated with oxidant HNO3 . Image 1 Highlights: Graphite felt (GF) was activated with HNO3 in a simple hydrothermal method at 90 °C. Oxygen-containing functional groups and hydrophilic of activated GF were increased. The activated GF showed better H2 O2 formation and TOC removal in electro-Fenton. The levofloxacin (LEV) degradation is mainly co-affected by.OH and M(OH). The apparent degradation rate constant of LEV achieved 0.40 min −1 with GF-9 cathode. Abstract : Greater H2 O2 generation and faster levofloxacin degradation achieved in the electro-Fenton process using graphite felt modified by low-temperature, hydrothermal treatment with HNO3 .